Herbal Treatment in Animal Reproduction - Perumal, P.; Veeraselvam, M.; Nahak, A. K. (International Journal of Bio-resource and Stress Management, 2013)
India has rich biodiversity of medicinal plants and traditional knowledge on herbal medicines to treat the animals and human beings. Reproduction disorders affect the production potential of the animals. Treatment of post partum disorders and infertility is a great task in animal reproduction especially in cattle. We are using the synthetic chemical drugs /medicines/ hormones to treat the reproductive disorders but it causes public health hazard and severe side effects on the animal reproduction. But the herbal drugs fewer side effects and more benefits and less health hazards. This paper describes the herbal medicines/ plants which are used in animal reproduction to cure reproductive disorders.